1998
DOI: 10.1016/s0022-5347(01)63784-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microwave Tissue Coagulator in Partial Nephrectomy for Renal Cell Carcinoma

Abstract: Partial nephrectomy using a microwave tissue coagulator can be safe and successful without renal pedicle clamping. However, the insertion line of the microwave electrode must be carefully determined for resection to be curative and safe, just as when making the cut line for conventional partial nephrectomy or tumor enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Naito et al showed the effectiveness of the microwave tissue coagulator for reducing blood loss when nephron-sparing surgery is performed without arterial occlusion. 7 This procedure was expected to prevent ischemic damage induced by vascular clamping. If so, residual renal function would be lower after conventional PNx compared to that after non-clamping PNx.…”
Section: Discussionmentioning
confidence: 99%
“…Naito et al showed the effectiveness of the microwave tissue coagulator for reducing blood loss when nephron-sparing surgery is performed without arterial occlusion. 7 This procedure was expected to prevent ischemic damage induced by vascular clamping. If so, residual renal function would be lower after conventional PNx compared to that after non-clamping PNx.…”
Section: Discussionmentioning
confidence: 99%
“…Although a major problem associated with traditional LPN is the control of bleeding from the resected site, hemostasis has been safely obtained by various procedures such as tumor resection after radiofrequency ablation [8] or microwave tissue coagulation [9,10] around a tumor, ultrasound dissection [11], hydro-jet dissection [11], and usage of argon beam coagulation [12] or a holmium:YAG laser [12] after tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…The microwave tissue coagulator, which was introduced by Tabuse [13], is useful for controlling parenchymal bleeding in solid vascular organs. Kagebayashi et al [9] and Naito et al [10] reported that this apparatus was also useful in PN, and some reports have described its effectiveness during LPN [14]. Microwaves cause thermal coagulation in renal tissues around the electrode, and a bloodless area is obtained through the vascular constriction caused by this thermal effect.…”
Section: Discussionmentioning
confidence: 99%
“…The technique remains largely experimental although some early clinical experience has been described [50,51]. The technique has also been described as an adjunct to open partial nephrectomy in order to provide a bloodless plane before resection [52].…”
Section: Microwave Thermotherapymentioning
confidence: 99%